Amostragem e análise de bioaerossóis: revisão histórica - Santos, Gustavo Bitencort dos (Universidade Federal de São Carlos, 2025)
The biological fraction of atmospheric particulate matter, composed of fungi, bacteria, viruses, pollen and cell fragments, plays a relevant role in air quality, climate and human health, especially in the context of respiratory inflammation, allergies and pathogen transport. Together with chemical pollution, these bioaerosols can aggravate pre-existing diseases and act as vehicles for viable microorganisms in indoor and outdoor environments. In this context, the present work aims to review, from a historical and comparative perspective, the sampling strategies and analytical techniques applied to bioaerosols in ambient air, with emphasis on performance, limitations and reported applications. The discussion covers both passive and active samplers, including gravitational collectors, volumetric slit samplers, impactors onto culture plates, liquid-phase devices, high-flow cyclones, filters, cascade impactors and personal samplers, highlighting aspects such as preservation of viability, sampled size range and temporal resolution. On the analytical side, the review encompasses methods ranging from microscopy and conventional culture to immunological assays, the use of chemical biomarkers and modern molecular and spectrometric techniques capable of providing greater taxonomic specificity and sensitivity. The studies examined show that there is no universal method and that each combination of collection and analysis involves trade-offs between temporal resolution, microbial viability, taxonomic detail, detection limit, cost and operational practicality. Therefore, the interpretation of results must consider the study objective, the sampled matrix and the biases associated with each approach, in order to promote data comparability and a critical reading of the findings.
Sampling and analysis of bioaerosols: a historical review
Keywords: Bioaerossóis; Viabilidade fúngica; Poluição atmosférica; Bioaerosols; Fungi viability; Air pollution; CIENCIAS EXATAS E DA TERRA::QUIMICA; 3. Saúde e Bem-Estar